Induction therapy with adalimumab plus methotrexate for 24 weeks followed by methotrexate monotherapy up to week 48 versus methotrexate therapy alone for DMARD-naïve patients with early rheumatoid arthritis: HIT HARD, an investigator-initiated study. Issue 6 (27th June 2012) - Detert, Jacqueline; Bastian, Hans; Listing, Joachim; Weiß, Anja; Wassenberg, Siegfried; Liebhaber, Anke; Rockwitz, Karin; Alten, Rieke; Krüger, Klaus; Rau, Rolf; Simon, Christina; Gremmelsbacher, Eva; et al.
Abstract : Objective: To investigate the long-term effects of induction therapy with adalimumab (ADA) plus methotrexate (MTX) in comparison with placebo (PBO) plus MTX in DMARD-naïve patients with active early rheumatoid arthritis (RA). Methods: Patients with active early RA (disease duration of ≤12 months) were randomly assigned to receive 40 mg ADA subcutaneously every other week (eow) plus MTX 15 mg/week subcutaneously or PBO plus MTX subcutaneously at 15 mg/week over 24 weeks. Thereafter, all patients received MTX monotherapy up to week 48. The primary outcome was the Disease Activity Score 28 (DAS28) at week 48. Secondary outcomes included proportions of patients in remission (DAS28<2.6), ACR responses, Health Assessment Questionnaire (HAQ) score and radiographic progression. Results: 87 patients were assigned to ADA/MTX and 85 patients to PBO/MTX. At baseline, DAS28 was 6.2±0.8 in the ADA/MTX and 6.3±0.9 in the PBO/MTX groups. At week 24, treatment with ADA/MTX compared with PBO/MTX resulted in a greater reduction in DAS28 (3.0±1.2 vs 3.6±1.4; p=0.009) and other secondary outcomes such as DAS28 remission rate (47.9% vs 29.5%; p=0.021) and HAQ (0.49±0.6 vs 0.72±0.6; p=0.0014). At week 48, the difference in clinical outcomes between groups was not statistically significant (DAS28: 3.2±1.4 vs 3.4±1.6; p=0.41). Radiographic progression at week 48 was significantly greater in patients administered PBO/MTX (Sharp/van der Heijde score: ADA/MTX 2.6 vs PBO/MTX 6.4; p=0.03, Ratingen score: 1.7 vs 4.2; p=0.01). Conclusions: A greater reduction in radiographic progression after initial combination therapy with ADA and MTX was seen at week 48, even after discontinuation of ADA treatment at week 24. This sustained effect was not found at the primary endpoint (DAS28 reduction).